PENGEMBANGAN MEDIA PEMBELAJARAN ANIMASI BERBASIS ANIMAKER PADA MATERI SISTEM PERNAPASAN MANUSIA TERHADAP HASIL BELAJAR SISWA - Khairani, Dwi; Huda, M. Komarul; Wilson Sitopu, Joni (Jurnal Metabio, 2023)
The development of Animaker-based animation media in Biology learning for grade XI of Yayasan Perguruan Keluarga Private High School is motivated by the lack of varied learning media, low effectiveness of media use, and inactive, lack of enthusiasm, and lack of student enthusiasm in learning. The research problem in this thesis is how to design Animaker-based animation media in Biology learning and how effective Animaker-based animation media is in Biology learning for grade XI of Yayasan Perguruan Keluarga Private High School. The research method used is Research and Development (R&D) with the Borg & Gall model. The subjects in this study were grade XI students of Yayasan Perguruan Keluarga Private High School, Pematangsiantar. Data collection techniques used expert validation sheets, validation, questionnaires, and observation. Then the data were analyzed using descriptive statistics. The research results show that Animaker based animation media was designed by: (1) identifying needs, (2) formulating basic competencies, (3) designing the media, (4) conducting validation and trials, with an average validation percentage obtained from material experts with an average percentage score of 93.84% in the Very Feasible category. Meanwhile, from media experts, an average percentage score of 95.29% was obtained in the Very Feasible category. Small-scale field trials obtained an average percentage score of 96.66% in the Very Feasible category. Large-scale field trials obtained an average percentage score of 85.77% in the Very Feasible category. (5) conducting media revisions. The effectiveness of Animaker-based animation media in social studies learning, with a percentage score of 100%, is categorized as very effective learning. This indicates that the Animaker-based animation media that has been developed can be used in the Pematangsiantar Family Education Foundation Private High School.